Pengaruh Topsoil dan Pupuk Organik Terhadap Panjang Sulur dan Jumlah Daun Tanaman Ubi Jalar (Ipomoea Batatas Lamb.) pada Media Tailing Emas: The Effect of Topsoil and Organic Manure Towards Length of Vein and Number of Laeves of Sweet Potatoes (Ipomoea Batatas Lamb.) in Gold Tailing - Ninda Meiditia Putri; Rhazista Noviardi; Reginawanti Hindersah; Pujawati Suryatmana (Jurnal Ilmu Tanah dan Lingkungan, 2021)
Processing of gold ore at artisanal gold mining in Kertajaya Village, Sukabumi, West Java produces residual processing waste or tailings which are generally disposed of into rivers or farm, stored in storage ponds or put in sacks for reprocessing. Due to the limited land owned by the community, the ponds and farm that were formerly dumped for tailings are widely used for farming. This study aims to determine the effect of adding topsoil and compost dose on the growth of sweet potato (Ipomoea batatas) at the maximum vegetative phase (7 Weeks after planted). The topsoil used in this study was taken from Kertajaya Village, which is an inceptisol soil type, while the sweet potato plant used was sweet potato clone MZ119. The research was conducted at the Ciparanje Experimental Farm, Faculty of Agriculture UNPAD, Sumedang from January to May 2020. This experiment used a factorial randomized block design with two factors, namely the topsoil-tailing ratio of 3 levels (30% w/w; 50% w/w; and 70% w/w) and compost doses of 4 levels (without compost (control); 10 tonnes ha-1; 20 tonnes ha-1; and 30 tonnes ha-1) with 3 replications. The results showed that the combination treatment of 70% topsoil: 30% tailings and compost dosage of 30 tonnes ha-1 could increase the length of sweet potato vein in the maximum vegetative phase which was 24.33 cm and the number of leaves was 54.33.